Checklist of the hornworts and liverworts of Java - Soderstrom, L.; Gradstein, Gradstein; Hagborg, A. (Phytotaxa, 2014)
In this checklist all hornworts and liverworts reports for Java are listed. The horn-and liverwort flora of the island consists of 568 known and accepted species (plus 39 invalid or illegitimate names). In addition 12 recorded species are considered dubious and another 111 species are excluded from the flora of Java. Most of the species are reported from West Java. The genus Stenolejeunea is synonymized with Lejeunea and we make the new combination Lejeunea thallophora (Eifrig) Gradst. and the new name Lejeunea propagulifera Gradst. (nom. nov. pro Trachylejeunea schiffneri Herzog; non Lejeunea schiffneri Steph. ex Schiffn.). A new synonym of Lejeunea papilionacea (Cardiolejeunea cardiantha R.M.Schust. et Kachroo syn. nov.) is proposed.